Lifetimes and rotation within the solar mean magnetic field. Issue 4 (11th February 2021) - Ross, Eddie; Chaplin, William J; Hale, Steven J; Howe, Rachel; Elsworth, Yvonne P; Davies, Guy R; Nielsen, Martin Bo
ABSTRACT: We have used very high-cadence (sub-minute) observations of the solar mean magnetic field (SMMF) from the Birmingham Solar Oscillations Network (BiSON) to investigate the morphology of the SMMF. The observations span a period from 1992 to 2012, and the high-cadence observations allowed the exploration of the power spectrum up to frequencies in the mHz range. The power spectrum contains several broad peaks from a rotationally modulated (RM) component, whose linewidths allowed us to measure, for the first time, the lifetime of the RM source. There is an additional broadband, background component in the power spectrum which we have shown is an artefact of power aliasing due to the low fill of the data. The sidereal rotation period of the RM component was measured as 25.23 ± 0.11 d and suggests that the signal is sensitive to a time-averaged latitude of ∼12°. We have also shown the RM lifetime to be 139.6 ± 18.5 d. This provides evidence to suggest that the RM component of the SMMF is connected to magnetic flux concentrations (MFCs) and active regions (ARs) of magnetic flux, based both on its lifetime and location on the solar disc.